Silence in the Second Language Classroom - King, J. author. aut Link
XII, 211 p.
Keywords: Why are second language learners in Japan's universities so silent? This book investigates the perplexing but intriguing phenomenon of classroom silence and draws on ideas from psychology, sociolinguistics and anthropology to offer a unique insight into the reasons why some learners are either unable or unwilling to speak in a foreign language.